The Relationship between Corporate Governance, Profitability, and Corporate Social Responsibility Disclosure on Firm Value in the Mining Sector - Rusdiah Hasanuddin (Brilliant International Journal Of Management And Tourism, 2023)
The mining sector faces increasing pressure to demonstrate sustainable business practices and environmental responsibility. Corporate governance, profitability, and corporate social responsibility (CSR) disclosure have emerged as critical factors influencing firm value, particularly in environmentally sensitive industries. This study aims to examine the relationship between corporate governance, profitability, and corporate social responsibility disclosure on firm value in mining companies listed on the Indonesia Stock Exchange (IDX). This quantitative study employed panel data analysis using a sample of 38 mining companies listed on IDX during 2018-2022, resulting in 190 firm-year observations. Firm value was measured using Tobin's Q ratio, while independent variables included board independence, audit committee effectiveness, return on assets (ROA), and CSR disclosure index. Multiple regression analysis with random effects was used to test the hypotheses. The findings indicate that corporate governance has a significant positive effect on firm value, with board independence (β = 0.247, p < 0.05) and audit committee effectiveness (β = 0.189, p < 0.05) both enhancing firm value. Profitability shows a strong positive effect (β = 0.412, p < 0.01), while CSR disclosure demonstrates a significant positive relationship with firm value (β = 0.234, p < 0.05). The model explains 71.3% of the variance in firm value (R² = 0.713). Corporate governance mechanisms, profitability, and CSR disclosure significantly enhance firm value in the mining sector. Companies should focus on strengthening governance structures, maintaining profitability, and expanding CSR activities to maximize shareholder value.